(untitled) - Allen, Virginia French (New York, N.Y., 1983)
Tactics for Listening is a comprehensive three-level listening series that features high-interest topics to engage and motivate students.
Keywords: English languag,Vocabulary; Study and teaching,Foreign students,Study and teaching